Asset Management Excellence : Optimizing Equipment Life-Cycle Decisions - Barry, Don M. (CRC Press, 2024)
"This is the third edition of Asset Management Excellence, Optimizing Equipment Life-cycle Decisions. The fundamentals of Asset Management are essential as Asset-intensive organizations look to technologies to help them compete. AI is becoming pervasive but must be confirmed and aligned with the fundamentals. This edition will provoke thought as each organization determines its next steps toward its new challenges in Asset Management"--